Philippine folk literature : The Myths - Eugenio, Daminia L. (Diliman, QC, 2001)
This collection of Philippine myths constitutes Volume 2 of the seven-volume Philippine Folk Literature Series being published by the U.P. Folkorists, Inc. To date.
Keywords: Folk Literature - Philippines; Legends - Philippines